Plant Biochemistry - Heldt, Hans Walter Heldt, Fiona (ACADEMIC PRESS, 2005)
This fully revised translation of the world-renowned German edition covers the complete and modern knowledge of plant biochemistry. The book presents the topic in a concise and simplified manner so that students can digest the message and gain a basic knowledge of the entire field of plant biochemistry, from photosynthesis (the synthesis of natural plant products) to all kinds of genetic engineering with its many commercial applications. Topics include cell structure and function, lipid and polysaccharide metabolism, nitrogen fixation, phloem transport, synthesis and function of isoprenoids, phenylpropanoids and other secondary metabolites, plant growth regulation and development. Heldt provides a comprehensive description of photosynthesis, primary and secondary metabolism, the function of phytohormones and molecular engineering. The text covers research findings until the end of 2003 and identifies areas of future research. There are extensive references to the most recent scientific literature. * Illustrated with two-color diagrams and well designed metabolic schemes * Plant metabolism presented in the context of the structure and function of the plant * Many examples of commercial applications for the protection and quality improvement of harvest crops, plant breeding, and the production of raw materials for industrial use * Coverage of the latest research findings.